A systematic review of research into aided AAC to increase social-communication functions in children with autism spectrum disorder. (2nd January 2017) - Logan, Kristy; Iacono, Teresa; Trembath, David
Abstract: Augmentative and alternative communication (AAC) interventions have been shown to be effective in supporting children with autism spectrum disorder (ASD) to communicate, particularly to request preferred items and activities. The aim of this systematic review was to examine the effectiveness of AAC interventions in supporting children to produce a broader range of communicative functions and determine the extent to which these interventions have been evaluated beyond immediate effectiveness to address maintenance, generalization, and social validity. A systematic search and application of inclusion criteria yielded 30 interventions that focused on communication functions beyond object requests. In many of the studies, flaws detracted from the certainty of evidence, and maintenance, generalization, and/or social validity were not addressed. Further research is needed to evaluate the extent to which AAC interventions can support children with ASD to communicate using a variety of communication functions, as well as to demonstrate sustained, transferable, and meaningful change.